Otonomi Kerja dan Employee Well-Being Pekerja Kreatif - Dwika, Wezha Prillanata; Rahmi, Tuti (EDU SOCIATA ( JURNAL PENDIDIKAN SOSIOLOGI ), 2024)
This study aims to determine the relationship between job autonomy and Employee well-being in creative workers in one of the animation studios in Padang city. This research applies a quantitative approach, with a correlational method. Respondents in this study were 45 workers with total sampling technique. The analysis method used is simple linear regression analysis. The results of this study indicate that there is a significant relationship between job autonomy and Employee well-being. The higher the autonomy of work, the higher the Employee well-being